Futsal Basic Technical Skills: Descriptive Study of Athletes at the Fordas Futsal Club - Bayu Insanistyo; Riko Setiawan; Yahya Eko Nopiyanto; Septian Raibowo; Andika Prabowo; Ibrahim Ibrahim; Ipa Sari Kardi (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2023)
Objective. Based on the observation results, it was found that the athletes of Fordas FC lacked mastery of basic technical skills in futsal. To address this issue, this research aims to determine the proficiency level of futsal basic technical skills in athletes at Fordas FC. Materials and Methods. This study is a form of quantitative descriptive research, which aims to describe the basic skills of futsal players, including passing, controlling, dribbling, and shooting. The subjects of this research are all 20 active athletes at Fordas FC. The research was conducted at the Futsal Field in Sumber Rejo Village, North Bengkulu, and the data collection technique used was the Basic Futsal Technique Skills Test. This test is specifically designed to measure the basic technical skills of futsal players. The collected data was analyzed using descriptive statistics in the form of percentages. Result. According to the research conducted, it was found that among the athletes of Fordas FC, 6 athletes (30%) were declared to have good basic futsal technical skills, 8 athletes (40%) were found to have adequate skills, 4 athletes (20%) were found to have poor skills, and 2 athletes (10%) were found to have very less skills. The average value of 82.31 indicates that the level of basic futsal technical skills of the athletes falls in the 74 < X ≤ 89 range. Conclusion. After conducting thorough research, it has been established that the athletes at Fordas FC club have an adequate level of basic futsal technical skills. The results of this study can prove to be highly beneficial for coaches and athletes as it provides comprehensive evaluation material to help them develop and enhance their fundamental technical abilities in futsal. With these findings, coaches can focus on specific areas of improvement, while the players can utilize these insights to work on their skills and become better at their game.